Pelatihan deteksi mental emosional dan tumbuh kembang anak menggunakan aplikasi DEMENAL - Heni Puji Wahyuningsih (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Mental emotional disorders and growth and development in elementary school children are often not known to parents or teachers. only sometimes children who experience growth and development deviations are known by ordinary people as a form of child delinquency, so that the guidance and treatment are not in accordance with what is needed. The purpose of implementing this community service is to provide elementary school teachers with knowledge and skills about child growth and development, provide knowledge about the growth and development of abnormal children or children with mental disorders, and train teachers to carry out early detection of mental growth and development in children and forms of deviation. In this activity, teachers train on how to conduct an early elementary assessment of mental emotional disorders and child development using the DEMENAL (Mental Emotional Detection) application. Evaluation is carried out after the training is complete. Elementary school teachers are given the task of screening students. It is said to be successful if 80% of elementary school teachers can do the screening. The results of the evaluation obtained that 85% of elementary school teachers were able to detect developmental and emotional mental disorders in elementary school children. However, there are still some elementary school teachers who are still confused and have not been able to detect mental and emotional disorders in children, so they still need more routine training to carry out screening so that they can understand and carry out smoothly and well. Furthermore, elementary school teachers are expected to be able to independently screen and screen mental disorders.